1981
DOI: 10.1139/f81-232
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Culture of Fish Stocks for Resource Management

Abstract: Examples of desired genetic changes produced in fish by selective breeding are contrasted with those of unintentional and often harmful genetic changes resulting from artificial propagation over prolonged periods, e.g. reduced longevity and reduced temperature tolerance. Evidence for undesired effects caused by the hatchery environment on captive fish stocks is also presented, e.g. precocity, inappropriate feeding behavior, and the risks posed by artificial rearing techniques are discussed. Methods for identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…However, recent studies Chittenden et al, 2010) have shown the presence of minor genetic differences when comparing wild specimens with hatchery, since currently genetic diversity of stocked fish has been expanded from the use of a high number of breeder individuals of wild origin. Thus, the low morphological variability found for the hatchery population likely is due to the high homogeneity of the tanks (Hynes et al, 1981;Taylor, 1986), where environmental pressures are constant, due to low disturbance frequency. The intraspecific polymorphism is typically caused by different selective pressures (Langerhans et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies Chittenden et al, 2010) have shown the presence of minor genetic differences when comparing wild specimens with hatchery, since currently genetic diversity of stocked fish has been expanded from the use of a high number of breeder individuals of wild origin. Thus, the low morphological variability found for the hatchery population likely is due to the high homogeneity of the tanks (Hynes et al, 1981;Taylor, 1986), where environmental pressures are constant, due to low disturbance frequency. The intraspecific polymorphism is typically caused by different selective pressures (Langerhans et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the amount of information available on both the ' population genetic principles ' and allozyme variation in fishes, applications of population genetics in practical fisheries management have not come up to the expectations of population geneticists of the early 1980s (Hynes et al, 1981;Ihssen et al, 1981;Krueger et al, 1981;MacLean & Evans, 1981;Spangler et al, 1981). Almost the only exception in this respect has been the management of Pacific salmonids, where genetic information is systematically used to get relative stock contribution estimates for fishing regulation purposes (Beacham et al, 1985(Beacham et al, , 1995Begg et al, 1999).…”
Section: Common Goal For Conservation and Fisheries Managementmentioning
confidence: 99%
“…A different conservation genetics problem is the imposition, knowingly or otherwise, of artificial selection upon a wild stock, leading to a state of domestication (Brisbin 1974). That fish respond by genetic change to selection in captivity is well established in salmonids (Vincent 1960;Donaldson 1970;Kincaid et al 1977) and other groups (Moav et al 1978;Hynes et al 1981). By relaxing natural selection, or replacing it with random or directional artificial selective forces, the fate of propagated populations may be jeopardized.…”
Section: Inbreeding Depression Inbreeding Depression Is Possiblymentioning
confidence: 99%